Complex technology of assimilation of the ball bearing steel and round billet production in conditions of RUP “Belarussian metallurgical works” - G. A. Anisovich; V. I. Timoshpolskij; V. V. Filippov; A. B. Steblov; M. P. Gulajev; V. A. Tishchenko; I. A. Trusova; I. L. Numeranov; D. V. Lenartovich (Литьë и металлургия)
There is worked out the complex (through) technology of production of high-quality ball bearing steel and proved the possibility of slugs production of square 125x125 mm and round section with diameter 130 mm, 115 mm and 90 mm in conditions of RUP '‘Belarussian metallurgical works”.